2022
DOI: 10.3390/agronomy12102253
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Molecular Evolution of the Magnesium Transporter (MGT) Gene Family in Citrullus lanatus and Cucumis sativus

Abstract: Magnesium transporters (MGTs) play a prominent role in the absorption, transportation, and storage of magnesium in plant cells. In the present study, MGT gene family members were identified and characterized into two species of Cucurbitaceae, including Cucumis sativus and Citrullus lanatus. Totals of 20 and 19 MGT genes were recognized in Citrullus lanatus and Cucumis sativus, respectively. According to their physicochemical properties, the members of each sub-class of MGTs in the species of Cucurbitaceae show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Low exon number was observed into BBX gene structure. It has been stated that genes with fewer exons are classified as early response genes and are induced faster [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low exon number was observed into BBX gene structure. It has been stated that genes with fewer exons are classified as early response genes and are induced faster [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exon number affects the diversity and the post-transcriptional processes of genes [ 55 ]. On the other hand, genes with low exon numbers are quickly induced and expressed in response to stimuli [ 55 , 56 ]. Conservative motif analysis found that there was a conservative motif, i.e., Motif1, contained by all SbDOFs, which is the motif that constitutes all the conservative domains of the sorghum DOF protein.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the evolutionary history of TLP genes in F. vesca differed from that of orthologous genes in other plant species. Although post-transcriptional modifications and variations in the transcripts of a gene are affected by the number of exons, it has been stated that genes with a low number of exons are induced faster in response to external [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%